Developments in Drug Addiction During COVID-19—An Austrian Perspective Based on a Clinical Sample - Fuchs-Leitner, Isabella; Yazdi, Kurosch; Gerstgrasser, Nikolas W.; Rosenleitner, Jan (Frontiers in Psychiatry, 2020)
Concerns about the negative consequences of the COVID-19 pandemic on people with substance use disorder (SUD) were raised by experts in the field around the world. Here we provide an Austrian perspective, discussing the impact of the pandemic on help-seeking patient with drug use disorder during the initial stage of the pandemic. Our perspectives are based on the situation as perceived at our clinical facility, and supported by original data collected from a small clinical sample of patients with drug use disorder (N=32). The viewpoints and related descriptive data include the perceived individual impact of COVID-19, as well as various aspects of drug use behavior and the Austrian drug market before and after the onset of the pandemic. The consequences for a subgroup of patients in opioid substitution treatment (N=24) are discussed. Surprisingly and in contrast to anticipated developments, we had the impression of a rather stable situation in Austria, at least at this early stage of the pandemic. The immediate impact of COVID-19 on these help-seeking patients with high levels of drug dependency seemed less severe than anticipated so far. Importantly, this observation might be a short-term effect for this already fragile group and careful monitoring of further developments are advised. In general, problematic drug use is associated with many health risk factors and finding appropriate long-term health care strategies has to remain a top priority. Our perspectives are restricted to observations from help-seeking patients at our clinic, and no conclusions for the general population can be directly drawn.